Uncertainty Theory: A Powerful Approach to Understanding Psychiatric Disorder. Issue 4 (2nd October 2017) - Strauss, John S.
Abstract : Objective : The tendency over the years in the mental health field has been to cling in circular fashion to one single domain after another, biological, psychological, or social, to explain severe disorder and not even to consider the data from the domain of focus that came before. This report notes that attempts to explore more complex biopsychosocial explanations that integrate the diverse domains have been generally ignored or foundered on the problems posed by the complexities involved and suggests an approach for moving beyond these problems. Method : A case history using two different formats highlights the degree to which the single domain models ignore one or another area of data. Results : Uncertainty theory is suggested as providing an important basis for exploring the complexities of a biopsychosocial understanding of mental health problems. Conclusions : This approach can provide a possible orientation to promote improved research, training, and treatment.